Hydrocolloid Use in the Treatment of Thermal Injury in a Dog - Gomide, Paula Regina Silva; Kobori, Laís Nogueira; Tetzner, Bruna Cardoso; Cunha, Larissa Cristina da; Santarosa, Bianca Paola (Acta Scientiae Veterinariae, 2020)
Background: Thermal injury is one of the most common type of skin damage found in clinical care, which results in a chronic wound. The treatment of chronic wounds should be specific, because it has a greater vulnerability of the organism to the external agents input. So, the treatment can be performed with covers to keep the lesion clean and free of contamination and also promote healing. Considering the amount of products available for the treatment, as well as the scarcity of studies in the literature proving the effectiveness of hydrocolloid in dogs, the aim of this case report was to describe a third degree burn wound in the sternal region of a dog treated with this material. Case: A 2-year-old non-castraded German Spitz dog, was attended in a private veterinary clinic located in Ribeirão Preto city, São Paulo state. The animal was submitted to general anesthesia for microneedling session to treat alopecia "X", and after the procedure, it showed a burn focus due to the resting time on the thermal mattress, affecting the entire sternal region. The choice treatment was a surgical debridement followed by second intention healing. The superficial crust of the wound was removed and the debridement of almost all the tissue that was not fit for healing was continued, resulting in a wide wound, with healthy tissue and only a small portion of devitalized musculature. On the same day, the daily dressing phase with crystal sugar was started, in order to promote the debridement of the remaining devitalized tissue and enable the appearance of granulation tissue, together with the asepsis provided by the chlorhexidine ointment (0.7 g/100mL). After five days, the wound presented with ascending granulation, with no signs of contamination and minimal residue of devitalized tissue. Then, the treatment with the hydrocolloid plate was chosen, which was cut and molded to the wound to allow the debridement with crystal sugar to continue in the devitalized muscle region. At this stage of treatment, the wound region where crystal sugar was used was cleaned and given a new dressing to be changed the next day, while the rest of the wound that had the hydrocolloid plate remained unmanaged for an average of five days, in order to improve animal welfare. After six days of dressing, the wound showed significant contraction, however the growth of the granulation tissue was exuberant. Four days after the first dressing change, the contraction of the wound proceeded at an accelerated rate, as well as the proliferation of granulation tissue, and on the 15th day of treatment with the hydrocolloid plaque, the wound was already quite reduced, with the maintenance of the tissue with healthy granulation, without contamination and with signs of good evolution. On the 27th day, the wound was practically healed, leaving a small central portion of the lesion. The scar tissue that involved the burn contributed to its retraction and accelerated the reepithelialization process. Finally, after 42 days, when the treatment finished, it was possible to notice hair growth and poor visibility of scar tissue. Discussion: The application of this type of dressing in the micro-needling burn injury suggested a better healing due the increase of keratinocyte proliferation and cell proliferation, since when used in the inflammation process, it accelerated the cleaning of purulent and necrotic tissues, stimulating the repair of clean wounds leading to good results and greater patient comfort. This study demonstrated that good healing could be achieved in alternative treatment using hydrocolloid dressing. In this method, healing proved to be more effective than conventional treatment, considering wound resolution and wound healing time.